THE IMPACT OF STRATEGIC HUMAN RESOURCE MANAGEMENT ON ORGANIZATIONAL PERFORMANCE - Syaiful Anwar; Erna Herlina (Jurnal Indonesia Sosial Teknologi, 2022)
Strategic Human Resource Management (SHRM) is concerned with the role human resource management systems play in firm performance, primarily focusing on the alignment of human resources as a means of gaining competitive advantage. The purpose of this research is to identify the Impact of Strategic Human Resource Management (SHRM) on Performance Organizations. The method used is literature by using an approach that uses specific examples from academic research on the impact of human resource strategy management on organizational performance. From this review, descriptions and conclusions will be drawn for later evaluation into new research that can be implied in the organization. The results and discussion are divided into 3, namely Human Resources as a Source of Competitive Advantage, the Strategic Role of Human Resources, and the impact of Strategic Human Resource Management (SHRM) on Performance Organizations. Based on the results of the analysis in this study it can be said that human resources are a source of sustainable advantage, while, traditionally, the costs associated with developing HR strategies as operational costs, these costs would be better off as an investment in assets. Then, the direct source found in this study is human resources which rarely have an effect on company performance.